Analysis of the Implementation of Family-Centered Care (FCC) on the Workload of Nurses in Pediatric Inpatient Areas - Supatmini, Erna; Ratnaningsih, Tri; Sajidin, Muhammad; Zamroni, Asroful Hulam (GLOBAL HEALTH SCIENCE GROUP, 2024)
The implementation of Family Centered Care requires collaboration between nurses and patient parents with a holistic approach and philosophy in preventing hospitalization. However, nurses in pediatric inpatient settings have high work responsibilities due to their complex role in the care process which must focus on pediatric patients and parents, which causes nurses to have an increasingly heavy workload. This study aims to analyze the implementation of Family Centered Care on nurses' workload. Method: This study used a cross-section design with a sample of 92 patients and pediatric nurses at RSUD Dr. Soetomo. This research used a purposive sampling technique for pediatric nurses and a simple random sampling technique for families of patients in the pediatric ward. Research data was collected through questionnaires from the variables of implementing family center care and nurse workload. Data on the variables of FCC implementation and workload were analyzed using a description test and the relationship between FCC implementation and workload was tested using a logistic regression test. Research data was processed using the description test and logistic regression test with a p-value ≤ 0.05. Results: The research results show that the implementation of family center care has a relationship with workload (0.001). Conclusion: The implementation of family-centered care can form a collaboration with patients and patient families thereby reducing the workload of pediatric nurses in providing nursing care.